Teknik Virtualisasi Penyimpanan pada Google Drive Guna Meningkatkan Keamanan dan Isolasi dalam Infrastruktur TI - Hatfina Rustamin; Afiqah Afiqah (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
Storage virtualization has become a key data management technology in the digital age, providing an efficient and secure solution for growing storage needs. Google Drive has adopted this technology to optimize user data management, including designing a security architecture, implementing data encryption in transit and at rest, and managing encryption keys. Access control using two-factor authentication (2FA). A reliable data backup and recovery system ensures fast recovery in the event of an accident. The technology enables additional features such as deduplication, compression, and version control that increase storage efficiency and flexibility. As a result, Google Drive offers secure, efficient and reliable cloud storage that allows users to manage data from multiple devices, confident that their data is protected.